2020
DOI: 10.1099/jmm.0.001161
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology, in vitro susceptibility and exoenzyme screening of Malassezia clinical isolates

Abstract: Introduction. Malassezia folliculitis (MF) and pityriasis versicolor (PV) are common dermatoses caused by Malassezia species. Their molecular epidemiology, drug susceptibility and exoenzymes are rarely reported in China. Aim. To investigate the molecular epidemiology, drug susceptibility and enzymatic profile of Malassezia clinical isolates. Methodology. Malassezia strains were recovered from MF and PV patients and healthy subjects (HS) and identified by sequencing analysis. The minimum inhibitory concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…In addition, KLKs activate multiple enzymes involved in TJ degradation (e.g., PAR2, matrix metalloproteases) and may be at least partially responsible for TJ weakness in SGR and AGR regions [ 21 , 22 , 23 ]. Moreover, region-specific bacteria and fungi (Propionibacterium and Malassezia on SGR; Corynebacterium, Proteobacteria, and Staphylococcus aureus on AGR skin [ 2 , 17 ]) influence the permeability barrier by producing exogenous serine and cysteine peptidases [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, KLKs activate multiple enzymes involved in TJ degradation (e.g., PAR2, matrix metalloproteases) and may be at least partially responsible for TJ weakness in SGR and AGR regions [ 21 , 22 , 23 ]. Moreover, region-specific bacteria and fungi (Propionibacterium and Malassezia on SGR; Corynebacterium, Proteobacteria, and Staphylococcus aureus on AGR skin [ 2 , 17 ]) influence the permeability barrier by producing exogenous serine and cysteine peptidases [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the nasolabial area, M. globosa (14%) was dominant, but three-fourths of the participants showed no growth of Malassezia 48 . Skin scraping analysis (culture method) showed that M. furfur (85%) and M. globosa (10%) were dominant in the thorax of 222 healthy Chinese subjects 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, preincubation with cytochalasin D or EDTA suppressed NLRP3 inflammasome activation and IL-1β release in this study, suggesting that yeast phagocytosis or M. globosa-derived proteases, at least metalloproteases, could be active in NLRP3 inflammasome activation of SZ95 sebocytes. Malasseziasecreted lipases, phospholipases and proteases may be important in pathogenicity and J o u r n a l P r e -p r o o f environmental adaption (Li et al, 2020). Since sebocytes express proteinase activated receptor 2 , the role of other M. globosa-derived proteases in NLRP3 inflammasome remains to be further studied.…”
Section: Supplementary Text 2 (Discussion)mentioning
confidence: 99%